Shaping Students’ Choices Through the 4Ps Model: An Examination of Marketisation Strategies in Tanzanian Higher Education Institutions - Vitus Johnson Matembo; Prosper Gabrieli; Paul Loisulie (Indonesian Journal of Social Science Education (IJSSE), 2025)
The increasing commercialisation of Higher Education Institutions (HEIs) has led to the widespread adoption of marketisation strategies to catch the attention of prospective students. In this regard, the current study examined how Tanzanian HEIs, both public and private, leverage the 4Ps (product, price, place, and promotion) model to shape the choices of prospective applicants. Employing a mixed methods research approach with an embedded design, qualitative and quantitative data were collected by using interview, questionnaire and document review. Semi-structured interviews were conducted with twelve selected staff members, including public relations officers (PROs) and registrars from six HEIs. Additionally, an online questionnaire was distributed to 100 students using convenience sampling. Quantitative data were summarized in descriptive tables and analysed using inferential statistics such as Chi-square and Kruskal-Wallis Test, while qualitative data were thematically examined. Qualitative analysis unveiled that HEIs in Tanzania employ diverse program offerings, brand identity enhancement, tuition-based revenue models, and industry partnerships to influence students' choices during the application process. Quantitative analysis displayed variances in the perceived effectiveness of marketing strategies utilized by Tanzanian HEIs. Significantly, differences between public and private universities were observed regarding the use of product and place as marketing strategies. These results suggest that Tanzanian HEIs have embraced a comprehensive marketing approach, integrating the 4Ps model to shape prospective students' decisions effectively. The study advocates for HEIs to enhance their brand identities collaboratively and expand their partnerships globally to enhance visibility in terms of price, product, promotion, and place as outlined in the 4Ps model. Public-private collaborations to enhance access and equity were found to be underutilized.